Deforestation and Migration - Britta Rude; Bennet Niederhöfer; Fabio Ferrara (CESifo Forum, 2021)
This article deals with the relationship between migration and deforestation. Based on the existing literature, it outlines how these factors can interact. It then illustrates these interactions using the example of three countries in South America that have experienced a particularly high deforestation rate in recent years: Brazil, Mexico and Paraguay. The study shows that the interactions between migration and deforestation are diverse and can have many reasons. Migration can be both a consequence and a cause of deforestation. Further research is needed to further understand possible measures that mitigate the potential negative effects of migration on forests on the one hand, and to reduce migration flows caused by deforestation on the other. We recommend a more productive use of forests and mechanisms that internalize associated externalities, such as CO2 generation or ecological values.
Keywords: 330